GP172 Should healthcare professionals routinely recommend a commercially available sleep movement monitor for babies?. (June 2019) - Wanniarachige, Dane; Murphy, Síofra; Titiloye, Alice; Ong, Wuey Qi; Hong, Yong Tze; Domah, Mohammud Javed; Hession, Ruth; Murray, Charlie; Molloy, Eleanor
Abstract : Background: Commercially available baby vital monitors have been successfully marketed towards parents, specifically as an intervention to prevent Sudden Infant Death Syndrome (SIDS). The aim of this study was to determine if evidence suggests that commercially available sleep movement monitors should be routinely recommended by healthcare professionals. Methods: A systematic literature review was undertaken to investigate the evidence for the efficacy of infant sleep monitors. The articles retrieved were then screened in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Literature search yielded five relevant articles, a majority (80%) relating to SIDS. Two studies showed the monitor was effective in accurately detecting cessation of breathing but could not comment on their efficacy with regards to SIDS prevention. A study of 53 infants using the Babysense monitor after an Apparent Life-Threatening Event (ALTE) found the monitor accurately detected apnoea and bradycardia when compared to the cardiorespiratory monitor 'Intellivue MP20 Junior' by Phillips. Two qualitative studies reported that such devices were appealing to mothers. Discussion: The medical effectiveness and reliability of these movement monitors is still a matter of controversy. Commercial monitors may be comparable to clinical cardiorespiratory monitors in terms of detection of apnoea and bradycardia. However, no article could conclude that sleep movement monitors are an effective method of SIDS prevention. Instead, healthcare professionals should emphasise interventions proven to reduce the risk of SIDS such as positioning infants on their back to sleep, or smoking cessation. Further limitations of the devices included a high rate of false alarms. Conclusion: The systematic review revealed that there is no evidence that commercially available sleep movement monitors can prevent SIDS. Therefore, sleep movement monitors should not be routinely recommended by paediatricians. However, some of the studies have shown the potential for other uses for these monitors. There is some evidence to suggest that they may be of use for monitoring specific cohorts of infants, including those who have had a previous ALTE, or have cardiorespiratory risk factors. Further research into these areas is required.